Cysticercosis: Hooked by a Hooklet on Fine Needle Aspiration Cytology—A Case Report. (19th August 2013) - Sawhney, Manav; Agarwal, Shubhra
Abstract : Cysticercosis is a systemic parasitic disease caused by the larval form of cestode T. solium . It has a worldwide distribution and is potentially harmful with variable clinical manifestations. The patient most commonly presents with subcutaneous and muscle involvement in the form of nodular lesions. The other most commonly involved sites include eye, brain, bladder wall, and heart. Cysticercosis can be diagnosed on serology, and radiologically but confirmatory diagnosis is based on histopathological examination of the involved tissue biopsy specimen. Fine needle aspiration cytology is a useful low-cost outpatient procedure tool for preoperative diagnosis of cysticercosis and is absolutely essential for diagnosis of the parasitic lesions in a peripheral hospital, one like ours.